. Determina el valor de x en las siguientes ecuaciones:

1) 5(x + 2) = 40

2) 2x(4x - 3) = 8x2 - 18

3) -2(x + 3) + 5(x - 2) = x + 1

4) 4(x + 3) - 2(-x + 3) = 6 - x

5) 8(x + 2) = 3(x - 5) - 7(x + 3)

6) a(x + 1) + 5a(x - 1) = 2(3b - 2a)

7) x(a + 1) - x(a - 1) = 2a + 4

8) (x + 2)(x - 5) = (x - 1)(x - 6)

9) (x - 8)(x + 1) = (x + 5)(x - 3)

10) (x + 1)(6x - 2) = (2x + 4)(3x + 2)

11) 2(x - 2)(x + 3) - (2x + 4)(x - 2) = 0

12) (6x + 10)(6x - 10) = 15 + (3x - 5)(12x + 5)

13) (2x + 3)(2x - 3) + 7 = 4(x + 2)(x - 2) + 2x

14) (x - 2)2 - (3 - x)2 = 1

15) (4x + 3)2 = 25(1 + x)2 - (4 + 3x)2

2

Respuestas

2012-10-10T07:28:44+02:00

1) 5x+10= 40

    5x=40-10

   5x=30

    x=6

2) y asi es el resto

2012-10-10T07:34:38+02:00

1) 5(x + 2) = 40

5(x + 2) = 40

(x + 2) = 8

x = 6

 

 

2) 2x(4x - 3) = 8x2 - 18

2x(4x - 3) = 8x^{2} - 18

x(4x - 3) = 4x^{2} - 9

x(4x - 3) = 4x^{2} - 9

4x^{2} - 3x = 4x^{2} - 9

(-3) x = - 9

3x = 9

x = 3

 

 

3) -2(x + 3) + 5(x - 2) = x + 1

-2(x + 3) + 5(x - 2) = x + 1

-2x -6 + 5x - 10 = x + 1

3x - 16 = x + 1

3x = x + 17

2x = 17

x = 17/2

 

 

4) 4(x + 3) - 2(-x + 3) = 6 - x

4(x + 3) - 2(-x + 3) = 6 - x

4x + 12 +2x -6 = 6 - x

6x + 12 - 6 = 6 - x

6x + 6 = 6 - x

6x = -x

7x = 0

x = 0

 

 

5) 8(x + 2) = 3(x - 5) - 7(x + 3)

8(x + 2) = 3(x - 5) - 7(x + 3)

8x + 16 = 3x - 15 - 7x - 21

8x + 16 = -4x - 36

12x = - 36 -16

12x = - 52

6x = - 26

x = - 13/3

 

 

6) a(x + 1) + 5a(x - 1) = 2(3b - 2a)

7) x(a + 1) - x(a - 1) = 2a + 4

8) (x + 2)(x - 5) = (x - 1)(x - 6)

9) (x - 8)(x + 1) = (x + 5)(x - 3)

10) (x + 1)(6x - 2) = (2x + 4)(3x + 2)

11) 2(x - 2)(x + 3) - (2x + 4)(x - 2) = 0

12) (6x + 10)(6x - 10) = 15 + (3x - 5)(12x + 5)

13) (2x + 3)(2x - 3) + 7 = 4(x + 2)(x - 2) + 2x

14) (x - 2)2 - (3 - x)2 = 1

15) (4x + 3)2 = 25(1 + x)2 - (4 + 3x)2